ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT SUKU AKIT TIDAK MELANJUTKAN PENDIDIKAN FORMAL DI DESA SOKOP KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Khotimah, Husnul; ', Hambali; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The Tribe Akit community is one of the remote communities in Riau, one of them is in Sokop Village, District of Rangsang Pesisir of Meranti Regency, where the Akit Tribe is included in Remote Indigenous Community (KAT). Based on the phenomenon that occurs Akit Tribe people who have dropped out of school for formal education from elementary school (SD), junior high school (SMP), High School (SMA), and Higher Education. Akit Tribe Society has the same rights as other tribes in getting education, this is in accordance with Article 31 Paragraph 1 of the 1945 Constitution which states that